Effects of Lactobacillus plantarum on growth traits, slaughter performance, serum markers and intestinal bacterial community of Daheng broilers. Issue 3 (2nd August 2021) - Song, Xiaoyan; Lin, Zhongzhen; Yu, Chunlin; Qiu, Mohan; Peng, Han; Jiang, Xiaosong; Du, Huarui; Li, Qingyun; Liu, Yiping; Zhang, Zengrong; Ren, Peng; Yang, Chaowu
Abstract: Probiotics are expected to be an ideal alternative for antibiotics in the poultry industry. This study aimed to investigate the effect of Lactobacillus plantarum on growth traits, slaughter performance, serum markers and intestinal bacterial community of Daheng broilers. A total of 2400 healthy one‐day‐old Daheng broilers were randomly divided into 5 groups with 6 replicates per group and 40 individuals per replicate. Birds in control group were fed a basal diet, and others were fed basal diets supplemented with 10 5, 10 6, 10 7 and 10 8  CFU/kg Lactobacillus plantarum, respectively. It turned out that adding Lactobacillus plantarum to diet could significantly improve the serum immune performance of broilers ( p  < 0.05), enhance the antioxidant capacity to a certain extent ( p > 0.05), but had no significant effect on growth traits and slaughter performance. Moreover, Lactobacillus plantarum could improve the diversity of intestinal bacterial community, but with the increase of addition concentration, the diversity would gradually decrease. In conclusion, Lactobacillus plantarum can be used as feed additive in broiler production, but whether it is more effective than antibiotics needs further investigation.